Aesthetics, ethics and trauma in the cinema of Pedro Almodóvar - Gutiérrez-Albilla, Julián Daniel (Edinburgh : Edinburgh University Press, 2017)
Reconceptualising AlmodÃ³Âđvar's films as theoretical and political resources, this innovative book examines a neglected aspect of his cinema: its engagement with the traumatic past, with subjective and collective memory, and with the ethical and political meanings that result from this engagement.
1. Im-Possibility of Not-Returning: Volver -- 2. Im-Possibility of Not-Sharing: Todo sobre mi madre -- 3. Im-Possibility of Not-Writing Otherwise: La mala education -- 4. Im-Possibility of Not-Succumbing: La piel que habito.
Includes bibliographical references (pages 177-214) and index.
Print version record.
JSTOR
Keywords: Almodóvar, Pedro -- Criticism and interpretation; Almodóvar, Pedro; Almodóvar, Pedro -- 1949-; Bibel; Motion pictures -- Spain -- History and criticism; Cinéma -- Espagne -- Histoire et critique; PERFORMING ARTS -- Reference; Motion pictures; Spain; Trauma; Criticism, interpretation, etc